Post‐disaster Cooperation Among Aid Agencies. (19th July 2017) - Heetun, Shameem; Phillips, Fred; Park, Sehee
Abstract : Natural and anthropogenic disasters affect ever‐larger populations. Effective cooperation among aid agencies is key to post‐disaster recovery. Studies in evolutionary game theory suggest two motives for one agency to cooperate with another: the other agency's reputation and the perceived probability of working together again in the future. This mixed method study collected data from decision makers in 30 aid agencies. The quantitative instrument, itself an evolutionary game, showed cooperation heavily influenced both by reputation and by interaction potential, with probable frequency of future interaction being a better predictor. Qualitative interviews affirmed the importance of both and showed learning, directives and reviews are subsidiary determinants of cooperation. This study answers—for the population of disaster aid managers—a controversial question in the evolution of cooperation. It offers guidance for agencies allocating training budget between technical skills (e.g. distributing medicines) and cooperation skills, with the aim of quickly aiding disaster victims. Copyright © 2017 John Wiley & Sons, Ltd.